CONFERENCE COMMITTEE/COMITE D'ORGANISATION DU CONGRES - Standera, Oldrich; Drummond, Fran; Gishler, John; Schick, Pat; Perusse, Lyse; Peters, Ronald; Linzmayer, Ferne; Nugent, Lynn; Pritchard, Sandy; Campbell, Donna; Goodman, H. J. A.; Simmons, Peter; et al. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2022)
See PDF